2010
DOI: 10.1161/atvbaha.109.193631
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Cognate Protein 70 Is Essential for Akt Signaling in Endothelial Function

Abstract: Objective-Heat shock protein 70s (Hsp70s) are molecular chaperones that protect cells from damage in response to various stress stimuli. However, the functions and mechanisms in endothelial cells (ECs) have not been examined. Herein, we investigate the role of Hsp70s, including heat shock cognate protein 70 (Hsc70), which is constitutively expressed in nonstressed cells (ie, ECs). Hsp72, a member of the Hsp70 family, protects cells, tissues, and organs from various harmful conditions in blood vessels. Previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 42 publications
3
52
0
Order By: Relevance
“…This highly conserved family of proteins function as molecular chaperones, and HSPs are involved in multiple cellular activities, including angiogenesis signaling (58,67,71). For instance, members of the HSP70 and HSP90 families have been reported to modulate angiogenesis in skeletal muscle (58,67).…”
Section: Heat Shock Proteins and Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…This highly conserved family of proteins function as molecular chaperones, and HSPs are involved in multiple cellular activities, including angiogenesis signaling (58,67,71). For instance, members of the HSP70 and HSP90 families have been reported to modulate angiogenesis in skeletal muscle (58,67).…”
Section: Heat Shock Proteins and Angiogenesismentioning
confidence: 99%
“…Second, repeated treatment with far infrared dry sauna increases skeletal muscle capillary density in a mouse model of PAD (1,40) and diabetes (26) and in rats treated with glucocorticoids (43). This angiogenic response in the heart and in skeletal muscle is closely coupled with increased expression of heat shock proteins (HSPs), molecular chaperones that are known to modulate the angiogenic process (40,67,71). Third, endothelial cells exposed to mild heat stress have an enhanced capacity for vascular tube formation, which is indicative of angiogenesis activity (60).…”
mentioning
confidence: 99%
“…26,27 This is juxtaposed to the RAG, which again exhibited increased proapoptotic proteins and decreased Bcl-2 ( Figure 3B). Although the exact mechanism for this apparent induction noted by exercising rats (Figure 4) is not entirely clear, such activation has been previously described in response to exercise-induced stress 17,28 and likely reflects increased VEGFR activation in response to exercise (eFigure 2 in the Supplement). Perhaps cells exposed to higher levels of stress during more strenuous exercise can escalate VEGF synthesis de novo, prolong VEGF messenger RNA half-life, or protect existing VEGF molecules from degradation and thus sustain VEGFR signaling (eFigure 3 in the Supplement).…”
Section: Discussionmentioning
confidence: 62%
“…These cascades also induce angiogenesis, increase vascular permeability, and enhance autocrine VEGF production. [14][15][16] Similarly, induction of various heat shock proteins promotes hypoxic tolerance and increases cell survival via modulation of the PI3K/Akt signaling 17 and other cell death-related cellular mechanisms. 18 Thus, creating an oxygen gradient elicits potent molecular responses that promote cell adaptation to injury and expedite wound repair.…”
mentioning
confidence: 99%
“…Hsc70 functions as a chaperone by trafficking proteins to different cellular compartments (Pilon and Schekman 1999) and is important in endocytosis (de Waegh and Brady 1989). Hsc70 is also involved in Akt (Shiota et al 2010;Chen et al 2011) and NF-κB signaling (Lim et al 2008) and has been shown to regulate the Dbl oncoprotein (Kauppinen et al 2005) and Bim mRNA (Matsui et al 2007). Importantly, Hsc70 also regulates cell survival (Powers et al 2008) and confers protection from several forms of cellular stresses, such as viral infection (Yan et al 2010), metabolic stress (Williams et al 1993), and oxidative stress (Chong et al 1998;Dastoor and Dreyer 2000;Su et al 1999).…”
Section: Introductionmentioning
confidence: 99%